Nevoid Basal Cell Carcinoma Syndrome: A Case Report and Review of Korean Cases - Jung, Eun-Joo; Shin, Hyokeun; Baek, Jin-A; Leem, Dae-Ho; Ko, Seung-O (Maxillofacial plastic and reconstructive surgery, 2014)
Nevoid basal cell carcinoma syndrome (NBCCS) is a rare autosomal genetic disease caused by a PTCH mutation. The disease is characterized by multiple basal cell carcinomas of the skin, multiple keratocystic odontogenic tumors (KCOTs) in the jaw, palmar and/or plantar pits, bifid ribs, ectopic calcification of the falx cerebri, and skeletal abnormalities. Early diagnosis is difficult in many cases because there may be a number of systemic symptoms. The purpose of this study is to report the case of a 12-year-old girl who was hospitalized with multiple KCOTs that occurred in the upper and lower jaws. Through characteristic clinical symptoms and radiologic findings, she was finally diagnosed as having NBCCS. This study also aims to organize the symptoms often observed in Korea using previously published case reports to provide useful information for the early diagnosis of NBCCS.